The demand for variety: a household production perspective - Daniel S. Hamermesh; Reuben Gronau (Institute for the Study of Labor (IZA), 2007)
Economists have devoted substantial attention to firms' supply of variety, but little to consumers' demand for variety. Employing the framework of home production, we trace differences in demand to differences in the opportunity costs of activities, which are associated with investments in human capital. Schooling alters time costs and changes the variety of activities household members choose. In time budgets from Australia, Israel, and West Germany we find that higher own and spouses' incomes raise variety (suggesting positive income effects). Education increases variety independent of income and earnings; part of its impact goes beyond a correlation of educational attainment with preferences for variety.
urn:nbn:de:101:1-2008040276
Keywords: 330; Produktdifferenzierung; Haushaltsproduktion; Zeitbudgetforschung; Theorie; Industriestaaten